Introduction of Mangrove Spectral Reflectance Pattern in Benoa Bay as An Indicator of Density Change Based on Landsat 8 Image - Kurniawati, Wiwik; Yuliara, I Made; Ratini, Ni Nyoman; Windarjoto, Windarjoto (BULETIN FISIKA; Vol 23 No 1 (2022): BULETIN FISIKA February EditionDO - 10.24843/BF.2022.v23.i01.p07, 2021)
Studies have been conducted on the introduction of spectral reflectance patterns as an indicator of changes in mangrove density distribution using landsat 8 imagery time series data, in benoa bay area, Bali. Methods and analyses use spectral reflectance and the Vegetation Normalized Difference Vegetation Index (NDVI). The results of determining the value of spectral reflectance show that, changes in mangrove spectral reflectance patterns in Benoa Bay from 2017-2020 have decreased and increased for each band. In the pattern of reflectance band 5 can be used as a reference there has been a reduction in mangrove area, where the smaller the value of reflectants in band 5 in 2017-2020 shows a reduction or change in mangrove density in the year is getting larger. Based on the data of NDVI vegetation index image distribution in 2017-2020 obtained wide cover per category that there is a reduction in mangrove area from 2017 to 2018 of 36.72 ha, but in 2019 mangrove area increased considerably from 2018 of 60.82 ha. In 2020 the mangrove area again experienced a fairly drastic reduction of 181.51 ha. The area recorded is still overgrown with mangroves in 2020 only amounting to 852.39 ha.